A comparative study of different methods of irrigation therapy in adults and children - I. B. Angotoeva; Ya. G. Starunova; D. P. Polyakov; A. K. Vinnikov (Медицинский совет, 2018)
Irrigation therapy is currently an integral part of the prevention and treatment of various ENT diseases. In and amongst all the variety of drugs of irrigation therapy, intranasal sprays are the most widely available. The article presents a comparative study of the intranasal spray characteristics. The advantages of using Marimer spray include minimal discomfort, jet sensation; the spray gets into the nasopharynx, but does not cause the Eustachian tube dysfunction.